2021
DOI: 10.1186/s12887-021-02561-y
|View full text |Cite
|
Sign up to set email alerts
|

Early immune responses and prognostic factors in children with COVID-19: a single-center retrospective analysis

Abstract: Background Early diagnostic indicators and the identification of possible progression to severe or critical COVID-19 in children are unknown. To investigate the immune characteristics of early SARS-CoV-2 infection in children and possible key prognostic factors for early identification of critical COVID-19, a retrospective study including 121 children with COVID-19 was conducted. Peripheral blood lymphocyte subset counts, T cell-derived cytokine concentrations, inflammatory factor concentration… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 27 publications
2
28
0
1
Order By: Relevance
“…Several studies have revealed that the hyper-inflammatory response induced by SARS-CoV-2 is a major cause of disease severity and death in adults [ 31 , 32 ]. Consistent with previous reports [ 6 , [33] , [34] , [35] ], and contrasting with our observations made in children with mild or moderate COVID-19, we found that severe disease was associated to a systemic inflammatory profile, revealed by the presence of high concentrations of inflammatory cytokines in plasma. Some of these cytokines remained elevated in the convalescent phase of infection, as observed in adults with severe COVID-19 [ 19 , 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have revealed that the hyper-inflammatory response induced by SARS-CoV-2 is a major cause of disease severity and death in adults [ 31 , 32 ]. Consistent with previous reports [ 6 , [33] , [34] , [35] ], and contrasting with our observations made in children with mild or moderate COVID-19, we found that severe disease was associated to a systemic inflammatory profile, revealed by the presence of high concentrations of inflammatory cytokines in plasma. Some of these cytokines remained elevated in the convalescent phase of infection, as observed in adults with severe COVID-19 [ 19 , 36 ].…”
Section: Discussionsupporting
confidence: 88%
“…We identified 9937 potentially relevant records from the literature databases and registers, and 1575 records from the additional searches. After screening the titles, abstracts and full texts, 56 studies (22 cohort studies, 9 case-control studies, and 25 case series) with a total of 79,104 patients were included [ [10] , [11] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , [75] , [76] ] ( Fig. 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 23 studies assessed risk factors for progression to severe or critical disease [ 25 , 26 , 28 , 30 , 33 , 36 , 42 , 49 , [51] , [52] , [53] , 55 , 59 , 60 , 61 , 63 , [65] , [66] , [67] , [68] , [69] , 71 , 76 ]. Neurological diseases ( OR =5.16, 95% CI 2.30 to 11.60, five studies, moderate-quality evidence) increased the odds of severe or critical disease.…”
Section: Resultsmentioning
confidence: 99%
“…Several genes have been identified for HLH (such as PRF1, UNC13D, STX11 and STXBP2) that encode molecules involved in the cytotoxicity of CD8-T cells and NK cells [94]. In this case, CD8-T cells and NK cells cannot lyse infected cells and this results in excessive immune stimulation (43). Another example is XIAP or NLRC4 deficiencies, which are associated with an overstimulation of the inflammasome [95].…”
Section: Multisystem Inflammatory Syndrome In Children (Mis-c)mentioning
confidence: 99%
“…However, similar or higher systemic levels of cytokine were observed in later studies of hospitalized children and adults [ 21 ]. On the other hand, high levels of inflammatory cytokines were observed in severe cases of pediatric COVID-19 [ 42 , 43 , 44 ] and also in children with mild disease [ 28 ]. A pivotal study by Pierce et al showed that children have a more intense nasal innate immune response, including higher levels of IFN-gamma and IFN-alpha, as compared to adults, suggesting that they may develop higher anti-viral responses at the mucosal level early on during infection [ 21 ].…”
Section: Immune Response To Sars-cov-2 Infection In Childrenmentioning
confidence: 99%